Determinants for elderly exercise intentions : a comparative study between exergame and traditional exercise. - Wu, Zumei. (2013)
The health concern of a rapidly ageing population is one of the most critical challenges faced by many countries globally. While the elderly understand the health benefits of exercise, the majority of them are sedentary and reluctant to exercise. Understanding factors that affect engaging the elderly in exercise would be helpful for individuals, communities and policy makers in exercise planning and promotion.